Determinants of cooperation for innovation in Brazilian companies - Avellar, Ana Paula Macedo de (2022)
The objective of this article is to analyze the determinants of cooperation for innovation in Brazilian innovative companies. The determinants of cooperation for innovation are investigated, considering the types of partners (productive chain, competitors, group and research institutions), the determinants of cooperation abroad and with institutions in the country for innovation, considering the types of partners. Based on PINTEC 2011 data, probabilistic models were estimated for a wide range of innovative companies. The results suggest that R&D expenditures, company characteristics, government support, main sources of information and obstacles to innovation explain cooperation for innovation.